Analisis Skala Usaha Udang Vannamei Di Desa Oneeha Kecamatan Tanggetada Kabupaten Kolaka - Muh Obi Kasmin; Aan Wilhan Juliatmaja; Andi Mariani Ramlan (Jurusan Agribisnis Fakultas Pertanian Universitas Sultan Ageng Tirtayasa, 2020)
It is important to measure the scale of the business because it will measure the success of a run business. This study aims to determine the effect of seed costs, feed costs and labor costs on the commercial income of Vannamei shrimp ponds and the scale conditions of prawn farming of Vannamei. Vannamei in Oneeha village, Tanggetada district. The sample determination in this study was done using the census method, while the data analysis method used in this study was multiple linear regression analysis with the Cobb-Douglass function. The results showed that the variable cost of seeds had a significant effect on the income level of the vannamei shrimp ponds business with a t-count of 4.879. While the variable feed costs and labor costs do not have a significant effect on the commercial income of shrimp ponds with tcount values of -0.926 and -0.893, respectively. The state of the commercial scale of the Vannamei shrimp ponds in Oneha village, Tanggetada subdistrict is increasingly commercial, as indicated by the total value of the regression coefficient which is greater than 1